Substantive Representation: Explaining the Adoption of Indigenous Rights Legislation in Latin America. - Schmid, Sven-Patrick (Latin American Research Review, 2025)
Indigenous peoples belong to the most underprivileged groups worldwide. To address this situation, countries in Latin America and beyond increasingly recognize Indigenous rights constitutionally. However, these constitutional rights are not implemented equally everywhere. This could relate to the corresponding ordinary law—or lack thereof. Here I ask, under which conditions are Indigenous peoples represented in ordinary legislation? To answer this question, I collected the original INDILEX dataset on the status of Indigenous peoples and their rights in the legislation of sixteen Latin American countries (1979–2018). Building on the political representation literature, I contrast descriptive representation with political allies, social movements, and favorable context factors as determinants of the substantive representation of Indigenous peoples. The analysis shows that leftist presidents and a broad constitutional mandate are key predictors of Indigenous rights legislation. The role of Indigenous civil society and democracy depends on the time frame and operationalization choice.